ð˜ˆð˜»ð˜°ð˜´ð˜±ð˜ªð˜³ð˜ªð˜ð˜ð˜¶ð˜® ð˜£ð˜³ð˜¢ð˜´ð˜ªð˜ð˜¦ð˜¯ð˜´ð˜¦ ASSOCIATION WITH STIMULATORS ON WHEAT CROP - Durlo, Luiza; Martin, Thomas Newton; Schonell, Alex T.; Burg, Giovane Matias; Rossatto, Anderson da Costa; Bruning, Lucas A. (REVISTA DE AGRICULTURA, 2020)
The objective of this research was to verify the association of stimulators and biofertilizers with the bacterium Azospirillum brasilense for wheat crop. Two experiments were carried out in which the mode and time of inoculation of A. brasilense bacteria were varied and different associations of growth stimulator and biofertilizer were tested. Number of plants per square meter, number of spikes per square meter, plant height, number of spikelets per plant, number of grains per spike, one thousand grain mass, hectoliter mass, and grain yield were evaluated. The association of A. brasilense with stimulators influenced grain yield. The use of stimulators in the seeds differed from the control in the variable â€œplant heightâ€, where the inoculated plants presented 2 to 3 cm in relation to the plants without inoculation. The use of A. brasilense associated